2000
DOI: 10.1007/s004210050067
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal responses to whole-body vibration in men

Abstract: The aim of this study was to evaluate the acute responses of blood hormone concentrations and neuromuscular performance following whole-body vibration (WBV) treatment. Fourteen male subjects [mean (SD) age 25 (4.6) years] were exposed to vertical sinusoidal WBV, 10 times for 60 s, with 60 s rest between the vibration sets (a rest period lasting 6 min was allowed after 5 vibration sets). Neuromuscular performance tests consisting of counter-movement jumps and maximal dynamic leg presses on a slide machine, perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
331
8
50

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 382 publications
(421 citation statements)
references
References 30 publications
32
331
8
50
Order By: Relevance
“…A small decrease in isometric torque was observed at knee angle of 60° in the WBV group and suggests that a certain fatigue was caused by vibration. This is further supported by other publications with comparable vibration settings (3-to-10 times 60-second periods of isometric squatting at 70-to-50° of knee flexion; vibration frequency: 30 Hz; vibration amplitude: 4-8 mm), reporting decreases in muscular strength after a single session of WBV (de Ruiter et al 2003;Erskine et al 2007;Jordan et al 2010) Conversely, some authors have reported strength increases immediately after WBV (Bosco et al 1999;Bosco et al 2000;Mc Bride et al 2010). However, this phenomenon only seems ephemeral, as suggested by its disappearance after a few minutes (Stewart et al 2009;Torvinen et al 2002).…”
Section: Torque-angle Relationshipsupporting
confidence: 68%
See 2 more Smart Citations
“…A small decrease in isometric torque was observed at knee angle of 60° in the WBV group and suggests that a certain fatigue was caused by vibration. This is further supported by other publications with comparable vibration settings (3-to-10 times 60-second periods of isometric squatting at 70-to-50° of knee flexion; vibration frequency: 30 Hz; vibration amplitude: 4-8 mm), reporting decreases in muscular strength after a single session of WBV (de Ruiter et al 2003;Erskine et al 2007;Jordan et al 2010) Conversely, some authors have reported strength increases immediately after WBV (Bosco et al 1999;Bosco et al 2000;Mc Bride et al 2010). However, this phenomenon only seems ephemeral, as suggested by its disappearance after a few minutes (Stewart et al 2009;Torvinen et al 2002).…”
Section: Torque-angle Relationshipsupporting
confidence: 68%
“…Earlier studies have found increased muscular strength and power after a single bout of vibration exercise (Bosco et al 1999;Bosco et al 2000). However, discrepant findings have since been reported and the immediate effects of WBV on neuromuscular performance are still debated.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Several studies have looked at the effects of WBV on muscle performance. However, the results are not clear and are sometimes contradictory (9,(13)(14)(15)17,21,22,25,35,38,39 AU7 ). The variability in the protocols used by different authors may explain the inconsistency of the results presented in published studies (13).…”
Section: Introductionmentioning
confidence: 99%
“…On application of vibration, the motor neuron may become synchronized and result in more force production of the muscle group [30,31]. Vibration may causes motor unit activation, synchronization between muscle spindles, reflexive recruitment of previously inactive motor units which leads to more force production for the exercise [12].…”
Section: Effect Of Interventions On Rommentioning
confidence: 99%